Redesigning rice photosynthesis to increase yield : proceedings of the Workshop on the Quest to Reduce Hunger : Redesigning Rice Photosynthesis, held in Los Baños, Philippines, 30 November-3 December 1999 /: proceedings of the Workshop on the Quest to Reduce Hunger : Redesigning Rice Photosynthesis, held in Los Baños, Philippines, 30 November-3 December 1999. (2000) - Unknown
No abstract available